Semiotics Analysis Of The Meaning Of Power In The Song “2+2=5” By Radiohead - Muhammad Muchalif; Muhammad Alfikri (LEGAL BRIEF, 2022)
Using Roland Barthes' semiotic theory, this study investigates the meaning of power in the lyrics of Radiohead's song "2+2=5". Roland Barthes examines the meaning of denotation, connotation, and myths regarding the meaning of truth in the song in this semiotic analysis. The approach is interpretive qualitative. Document study is the collection technique used to obtain data from various sources relevant to the research. The research findings based on the denotative meaning indicate the existence of a condition in which a person can be made to believe anything, even when the truth is obvious. As a result, some people will take advantage of this to exert control over others. The connotation result is someone who prefers false reality to the truth every day. While the myth's meaning is that people in power believe they are not getting the attention they deserve despite having people under their control who they believe need it more. The authority figures' ideas shift from wanting to attract attention to believing their own lies. In this case, the author emphasizes that power can be extremely dangerous if not used correctly.